Political Use of the Photograph: A Semiotic Study of the Photograph of Al-Kadhimi's Visit to Fallujah on the Anniversary of the Victory Over ISIS - Mohammed, Ahmed Hameed; Al-rawi, Bushra Jameel (ALBAHITH ALALAMI, 2023)
The research aims to determine what a photograph intends to convey as a visual text. Photographs are not captured randomly, especially those of politicians. Each photograph carries a message, even if interpretations of that message vary from person to person. The research adopts a methodology based on semiotic analysis, applying Laurent Gervero's model to analyze a photograph of the Iraqi Prime Minister Mustafa Al-Kadhimi's visit to Fallujah on the anniversary of the victory over ISIS. The photographs in question constitute a visual language built upon a sequence of iconic symbols and signs. These elements coalesce to give rise to an image centered around a particular theme, one designed to convey a precise message to the intended audience. Additionally, they serve as a window into the photographer's ideology, as they make deliberate choices regarding which aspects of the event to capture through their camera lens.The research yields several results, including: The ideas and meanings contained in the photograph, both in form and content, fall within the framework of political marketing for the personality of the Iraqi Prime Minister Mustafa Al-Kadhimi, highlighting him as a strong and sharp personality. The rhetoric of the photograph emphasizes unity, rejection of sectarianism and nationalism. The diversity and functional progression of Al-Kadhimi's career in journalism and historical documentation helped him gain experience in the art of appearance and influence on the recipient, in addition to his previous work in the sensitive field of intelligence.